Developing Cotton IPM by Conserving Parasitoids and Predators of The Main Pest - Nurindah Nurindah; Dwi Adi Sunarto (Jurnal Entomologi Indonesia, 2011)
On early development of intensive cotton program, insect pests were considered as an important aspect in cotton cultivation, so that it needed to be scheduled sprays. The frequency of sprays was 7 times used 12L of chemical insecticides per hectare per season. Development of cotton IPM was emphasized on non-chemical control methods through optimally utilize natural enemies of the cotton main pests (Amrasca biguttulla (Ishida)Helicoverpa armigera (Hübner)). Conservation of parasitoids and predators by providing the environment that support their population development is an act of supporting the natural enemies as an effective biotic mortality factor of the insect pests. The conservation could be done by improving the plant matter and cultivation techniques that include the use of resistant variety to leafhopper, intercropping cotton with secondary food plants, mulch utilization, using action threshold that considered the presence of natural enemies, and application of botanical insecticides, if needed. Conservation of parasitoids and predators in cotton IPM could control the insect pests without any insecticide spray in obtaining the production of cotton seed. As such, the use of IPM method would increase farmers’ income.